EFEKTIVITAS DEEP BACK MASSAGE DAN EFFELURAGE MASSAGE TERHADAP PENURUNAN INTENSITAS NYERI PERSALINAN KALA I FASE AKTIF PADA IBU PRIMIPARA DI PUSKESMAS BATANG - Sri Resky Mustafa; Khalida Z. S (Stikes Graha Edukasi Makassar, 2022)
Objective: This study aims to determine the effectiveness of deep back massage and effleurage massage on reducing the intensity of labor pain in the active phase of the 1st stage of primiparous mothers at the Batang Health Center. Methods: This study uses a quantitative design with the method experimental quasi by using one shot with case study. Results: The results showed that the effleurage massase group was more effective than the deep back massage group, which can be proven by the value of the Mann Withney test p = 0.006 . This can be seen from the post test value of the effleurage massase technique with a total of 16 respondents, of which 13 respondents were in moderate pain intensity and 3 respondents were in severe pain. While the deep back massage technique with a total of 16 respondents, where and 11 respondents were at moderate pain level, and 5 respondents were at severe pain intensity. Discussion: Giving effleurage massase and deep back massage techniques is very effective because after being given the treatment, the results show a decrease in pain intensity in pregnant women who experience pain during the first stage of labor in the active phase. Conclusion: The administration of the effleurage massage technique is more effective than the deep back massage technique in reducing the intensity of labor pain in the active phase of the first stage in primiparous mothers at the Batang Health Center. Suggestion: It is expected that midwives and maternity nurses can provide health care in the form of deep back massage and effleurage massage repeatedly to primiparous mothers who experience labor pain in the first stage of active phase